FOUCAULDIAN SURVEILLANCE IN PROBITY AUDIT: DECODING STRATEGIES TO PREVENT PROCUREMENT FRAUD - Ramadhan, Muh. Syahru; Iswati, Sri (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2025)
Corruption cases in the procurement of goods and services continue to occur. This study aims to examine the effectiveness of the implementation of probity audits in preventing fraud in the procurement of goods and services. This study uses qualitative approach with participants from the DKI Jakarta Provincial and the Dompu Regency Inspectorate. The results of the study indicate that the probity audits carried out by the DKI Jakarta Provincial Inspectorate and the Dompu Regency Inspectorate during 2023 and 2024 have not been optimal. This is because the probity audit process still uses the data sampling method, thus limiting comprehensive fraud detection. Furthermore, this study found that the lack of qualified auditors and inadequate technological support hindered audit effectiveness. This study contributes to the academic literature and audit and oversight practices by integrating the concept of Foucauldian oversight into the context of integrity audits to prevent fraud in government procurement.